The precision structural regulation of PLLA porous scaffold and its influence on the proliferation and differentiation of MC3T3-E1 cells. Issue 17 (21st November 2016) - Ge, Min; Xue, Li; Nie, Taotao; Ma, Haiyun; Zhang, Jinchao
Abstract: A thermal-induced phase separation combined sugar template method was used to fabricate the Poly (L-lactide) acid (PLLA) scaffolds with precisely regulated porous structure. The effect of tuned porous structure of scaffolds on osteoblasts proliferation and differentiation was investigated. The results showed that the pore diameters (200–300, 300–400, 400–500 μm), porosity and interconnectivity of PLLA scaffolds can be accurately controlled indicated by scanning electron microscope. The results of cell experiments showed that the porous structure including the pore size and interconnectivity of scaffolds dramatically influence the cell proliferation and differentiation. The scaffold with pore diameter of 400–500 μm exhibited the highest cell viability and alkaline phosphatase activity among all the scaffolds for the MC3T3-E1 cells. The higher cell proliferation and biocompatibility observed in the 400–500 μm scaffold indicated the high selectivity for MC3T3-E1cells on the pore size of scaffold in tissue engineering. The precise control of the porous structure of scaffold may better guide the cell–matrix interaction in the future research.